Applied econometrics : a modern approach using EViews and Microfit - Asteriou, Dimitrios; Hall, S. G. (New York, N.Y. : Palgrave Macmillan, 2007)
This new econometrics text deals specifically with the use of econometric software. The text takes the reader from the various forms of econometric data (time series, cross sectional and panel), through their formatting in electronic media (eg ASCII) to their transfer to and use in widely used software packages--Excel, Microfit and Eviews. Most economics degrees now require students to use relevant software to test econometric models and this text illustrates clearly how this is to be done.
Includes bibliographical references and index.
oif 27/06/14
Loan
Keywords: Econometrics; Economics